PENERAPAN TEKNOLOGI KEMASAN KEDAP UDARA UNTUK PRODUKSI PEWANGI MOBIL BERAROMA TAHAN LAMA - Galvin Leong; Lukman Sujardi (Jurnal Serina Abdimas, 2026)
The high activity and mobility of private vehicle users trigger a high demand for optimal cabin atmosphere quality. In the market context, car air freshener products generally face two critical problems: the rapid evaporation of scent compounds, resulting in short durability, and a lack of aesthetic value in packaging that tends to appear standard. This issue compels consumers to make frequent repeat purchases, impacting both efficiency and the driving experience. This project, which is part of the Merdeka Belajar Kampus Meredeka (MBKM), is here to provide an innovative and sustainable solution through the Implementation of Vacuum Sealing Packaging Technology in a car air freshener production line. The core innovation in this activity lies in the packaging technology aspect. The product specifically utilizes vacuum-sealed packaging during the storage phase before the product is put into use. The implementation of this technology aims to minimize the contact of essential oil compounds with oxygen, maintain the stability of aroma molecules, and prevent the degradation and premature evaporation of the natural fragrance formula used. The MBKM implementation methodology focuses on Technology Implementation and Innovation Commercialization, executed through several main stages: 1) Functional Product Analysis (to determine the safe and effective composition of the aroma formula), 2) Implementation of Vacuum Sealing Packaging Technology (as the key product differentiator), 3) Aesthetic Branding Design that is aligned with a modern lifestyle, and 4) Product Socialization and Marketing through digital channels and communities. The result of this activity is a car air freshener product successfully commercialized with both functional and visual advantages. The product is proven capable of retaining scent intensity and quality optimally for a longer period, thanks to the applied packaging technology. This success demonstrates that the combination of packaging technology innovation and aesthetic product design can meet consumer demand for both functional and decorative products, opening up significant market opportunities for student entrepreneurship. Tingginya aktivitas dan mobilitas pengguna kendaraan pribadi memicu tingginya permintaan terhadap kualitas suasana kabin yang optimal. Dalam konteks pasar, produk pewangi mobil yang beredar secara umum sering kali menghadapi dua masalah kritis: cepat menguapnya senyawa aroma sehingga daya tahannya singkat, dan kurangnya nilai estetika pada kemasan yang cenderung terkesan standar. Permasalahan ini mendorong konsumen untuk sering melakukan pembelian ulang, yang berdampak pada efisiensi dan pengalaman berkendara. Proyek ini, yang merupakan bagian dari Merdeka Belajar Kampus Merdeka (MBKM), hadir untuk memberikan solusi inovatif dan berkelanjutan melalui Penerapan Teknologi Kemasan Kedap Udara dalam lini produksi pewangi mobil. Inovasi utama dalam kegiatan ini terletak pada aspek teknologi pengemasan. Produk ini secara spesifik menggunakan kemasan vacuum-sealed (penyegelan kedap udara) pada tahap penyimpanan sebelum produk digunakan. Penerapan teknologi ini bertujuan untuk meminimalisasi kontak senyawa essential oil dengan oksigen, menjaga stabilitas molekul aroma, serta mencegah degradasi dan penguapan dini dari formula wewangian alami yang digunakan. Metode pelaksanaan MBKM ini berfokus pada Penerapan Teknologi dan Hilirisasi Inovasi, yang dijalankan melalui beberapa tahapan utama: 1) Analisis Fungsional Produk (untuk menentukan komposisi formula aroma yang aman dan efektif), 2) Implementasi Teknologi Kemasan Kedap Udara (sebagai diferensiasi produk), 3) Perancangan Branding Estetik yang dan sesuai gaya hidup modern, serta 4) Sosialisasi dan Pemasaran Produk melalui kanal digital dan komunitas. Hasil dari kegiatan ini adalah produk pewangi mobil yang berhasil terhilirisasi dengan keunggulan fungsional dan visual. Produk terbukti mampu mempertahankan intensitas dan kualitas aroma secara optimal lebih lama berkat teknologi kemasan yang diterapkan. Keberhasilan ini menunjukkan bahwa perpaduan antara inovasi teknologi kemasan dan desain produk yang estetik mampu menjawab kebutuhan konsumen akan produk fungsional dan sekaligus dekoratif, membuka peluang pasar yang signifikan bagi wirausaha mahasiswa.